Порівняльна характеристика регенерації стегнової кістки щурів при інтрамедулярному остеосинтезі з використанням медичної сталі та вуглець-вуглецевого композитного матеріалу - Чорний, Владислав Вадимович; Богданов, Павло Валерійович; Chornyi, V. V.; Bohdanov, P. V. (Запорізький державний медичний університет, 2022)
Мета роботи – порівняти морфологічні особливості регенерації стегнової кістки щурів при інтрамедулярному остеосинтезі з використанням медичної сталі та вуглець-вуглецевого композитного матеріалу. Матеріали та методи. Шляхом оперативного втручання дослідним тваринам моделювали перелом стегнової кістки. Усіх тварин поділили на дві групи: у першій для інтрамедулярної фіксації уламків використовували медичну сталь, а в другій фіксацію уламків кістки виконували за допомогою вуглець-вуглецевого композитного матеріалу. Під час дослідження дотримувались Директиви 2010/63/ЄС з захисту тварин Європейського Парламенту, принципів Гельсінської Декларації та Закону України № 3447-IV «Про захист тварин від жорстокого поводження». Використовуючи морфологічні, морфометричні, гістологічні, гістохімічні, імуногістохімічні та рентгенологічний методи дослідили кістковий регенерат на 30 добу, через 6 і 12 місяців після оперативного втручання. Вивчали експресію імуногістохімічних маркерів CD-34 і Кі-67 на клітинах регенерату з використанням програми ImageJ. Статистичний аналіз результатів виконали методами варіаційної статистики з використанням програми Statistica 13.0. The aim of this study was to compare the morphological features of rat femoral bone regeneration during intramedullary osteosynthesis using medical steel and carbon-carbon composite material. Materials and methods. All animals were divided into two groups. A fracture of the thighbone was simulated by surgical intervention. In the first group, medical steel was used for intramedullary fixation of fragments; in the second group, fragments were fixed using a carbon-carbon composite material. The morphological, morphometric, histological, histochemical, immunohistochemical and X-ray methods was used, the bone regenerate was studied on the 30th day, 6 and 12 months after the surgical intervention. There were established expression of immunohistochemical markers CD-34 and Ki-67 using the ImageJ program. The statistical analysis of the obtained results was performed by the methods of variational statistics using the program Statistica 13.0. Results. In the group of animals where composite material was used, on the 30th day after surgery, a statistically significant increase in the expression of the relative area occupied by CD-34+ structures compared to the second group of animals was established (4.80 ± 0.40 in the group in which the composite material was used and 2.80 ± 0.30 in group in which the medical steel was used). Also a statistically significant increase in the expression of the Ki-67+ marker was established (5.20 ± 0.36 in the group in which the composite material was used and 2.48 ± 0.32 in group in which the medical steel was used). With inspection microscopy, faster rates of osseointegration and regeneration of the fracture site were observed in the group of animals in which the composite material had been used compared to the other group of animals due to the stimulation of vascular endothelium growth. The data of the histological examination coincide with the data of the X-ray examination at all the periods of observation.
Comparative characteristics of the regeneration of the femur bone of rats at intramedullary osteosynthesis using medical steel and carbon-carbon composite material
Чорний В. В. - ORCID ID: 0000-0003-0902-7616; Богданов П. В. - ORCID ID: 0000-0002-1533-6370.
Keywords: регенерація; перелом кістки; інтрамедулярний остеосинтез; композитний матеріал; вуглець; regeneration; bone fracture; intramedullary fracture fixation; composite material; carbon